2019
DOI: 10.1002/1878-0261.12524
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing in human cancer cells is modulated by the amiloride derivative 3,5‐diamino‐6‐chloro‐N‐(N‐(2,6‐dichlorobenzoyl)carbamimidoyl)pyrazine‐2‐carboxide

Abstract: Alternative splicing (AS) is a process that enables the generation of multiple protein isoforms with different biological properties from a single mRNA. Cancer cells often use the maneuverability conferred by AS to produce proteins that contribute to growth and survival. In our previous studies, we identified that amiloride modulates AS in cancer cells. However, the effective concentration of amiloride required to modulate AS is too high for use in cancer treatment. In this study, we used computational algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…One of these derivatives; BS008, was found to induce cell cycle arrest and apoptosis in hepatocellular carcinoma cells, induce alternative splicing of apoptotic genes and decrease tumor growth in a hepatocellular carcinoma mouse model. Previously seen effects of amiloride on SR and hnRNP proteins were confirmed and extended in this study, together suggesting that amiloride-like compounds modulate AS in cancer cells via a diversity of effects on mRNA splice factors, regulating kinases and histone modifications [306].…”
Section: Hypothesis-driven Identification Of Spliceosome Inhibitorssupporting
confidence: 81%
See 1 more Smart Citation
“…One of these derivatives; BS008, was found to induce cell cycle arrest and apoptosis in hepatocellular carcinoma cells, induce alternative splicing of apoptotic genes and decrease tumor growth in a hepatocellular carcinoma mouse model. Previously seen effects of amiloride on SR and hnRNP proteins were confirmed and extended in this study, together suggesting that amiloride-like compounds modulate AS in cancer cells via a diversity of effects on mRNA splice factors, regulating kinases and histone modifications [306].…”
Section: Hypothesis-driven Identification Of Spliceosome Inhibitorssupporting
confidence: 81%
“…While amiloride induced cell cycle arrest and apoptosis in leukemic cells [ 305 ], effective concentrations were too high to translate its use into the clinic. Therefore, an elegant study employing computational drug design identified potential molecular targets (SNRP70 and hnRNPI) of amiloride and this aided the development of amiloride derivatives with optimized docking properties onto the putative targets [ 306 ]. One of these derivatives; BS008, was found to induce cell cycle arrest and apoptosis in hepatocellular carcinoma cells, induce alternative splicing of apoptotic genes and decrease tumor growth in a hepatocellular carcinoma mouse model.…”
Section: Therapeutic Targeting Of Dysregulated Mrna Splicing In Cancermentioning
confidence: 99%
“…RNA splicing factors have emerged as a new class of oncoproteins and tumor suppressors, which lead to disease progression by regulating RNA subtypes in landmark cancer pathways [ 4 ]. Therefore, dysregulation of alternative RNA splicing is the foundation of cancer and provides a potentially rich source for new therapeutic targets [ 5 , 6 ]. Studies have reported that alternative splicing can significantly change the coding region of drug targets and play an important role in the treatment of tumor resistance [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The spliceosome machinery has been directly targeted as a potential global anticancer therapy [ 139 ]. Amiloride, a drug typically used with other medications to treat high blood pressure, treatment of cells results in changes in alternative splicing [ 140 , 141 ]. Numerous oncogenic genes, including BCL-X , HIPK 3 and RON/MISTR1 , had altered alternative splicing patterns after treatment of cells with amiloride, most likely as a result of hypophosphorylation of SRSF1 [140,141].…”
Section: Modulation Of Splicing Factorsmentioning
confidence: 99%
“…Additionally, it has been discovered that certain small compounds can prevent the phosphorylation of particular SR proteins, and this way regulating specific alternative splicing events [ 154 ]. General splicing inhibitor, amiloride, was shown to cause hypophosphorylation of SRSF1 [ 140 , 141 ].…”
Section: Modulation Of Splicing Factorsmentioning
confidence: 99%